FUNGSI WEBSITE SEBAGAI MEDIA DALAM MENUNJANG TRIPOTENSI MAHASISWA ILMU KOMUNIKASI FAKULTAS DAKWAH DAN KOMUNIKASI UIN ALAUDDIN MAKASSAR - Asni Djamereng (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2021)
This study discusses the function of the website of the Communication Studies Program, Faculty of Da'wah and Communication at UIN Alauddin Makassar as a medium in supporting the tri potency of students in Communication Science, Faculty of Da'wah and Communication, UIN Alauddin Makassar. The purpose of the research is to find out the function of the website of the Department of Communication Science, Faculty of Da'wah and Communication, Alauddin University Makassar in supporting student tri potency, as well as to find out the efforts made to support tri potency and attract students' interest in using the website. This type of research is descriptive qualitative research using data collection methods of observation, interviews, and documentation. There are three stages of data processing and analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that the function of the website of the Communication Studies Study Program, Faculty of Da'wah and Communication, apart from being a medium of information through the news presented, can also function as a medium in supporting the tri potency possessed through the work produced. News Column, Student Talk, Inspiration, and Community are filled by Communication Science students who become reports through the results of the selection made by the website manager.